Active and Passive Therapy of the Upright Posture and Its Influence on the Hemodynamics of the Upper Limbs - Ivana Jelínková; Robert Válka; Monika Šorfová (Karolinum Press, 2014)
Poor posture negatively influences the hemodynamics of the upper extremities. In clinical practice, this is known as Thoracic outlet syndrome. Poor posture leads to muscle imbalances which are solved with the active exercise or using the passive technique - taping. This work is an experimental pilot study dealing with the kinematics and taping of the cervical-thoracic spine and their influence on the hemodynamics of the upper extremities. Ten subjects aged 26 ± 2 years, weight 56 ± 4 kg, height 161 ± 8 cm (mean ± SD) without pathology or injury of the shoulder girdle and spine were recruited. First part of subjects (5 persons) externally rotated the arms. During this exercise the kinematic analysis was used for determining the extension of the thoracic spine. Another part of subjects (5 persons) used the taping of rhomboids and pectoralis minor muscles. The hemodynamics of the axillary artery was determined with the sonography at both groups. The taping improves the hemodynamics of the upper extremities easier than the active exercise, which should be done with the control of the physiotherapist. Aktivní a pasivní terapie napřímení a jeho vliv na hemodynamiku horních končetin Chabé držení těla vede ke změnám nervově-cévního zásobení horních končetin. Toto je popisováno v klinické praxi jako syndrom horní hrudní apertury. Vadné držení těla je doprovázeno svalovými dysbalancemi, které jsou optimalizovány aktivním cvičením nebo s využitím pasivní techniky - tapingu. Tato práce je experimentální pilotní studií, která se zabývá kinematikou a tapingem cervikothorakálního přechodu a jejich vlivem na cévní zásobení horních končetin. Deset probandů (26 ± 2 let, 56 ± 4 kg, 161 ± 8 cm) bez patologie a zranění pletence ramenního a páteře podstoupilo měření. První část probandů (5 osob) prováděla cvičení - zevní rotace paže. Během tohoto cvičení byla snímána kinematickou analýzou (Qualisys) extenze hrudní páteře. U druhé části probandů (5 osob) byl použit taping rhomboideálních a malého prsního svalu. U obou skupin byla použita sonografie k určení krevního toku arterií axillaris. Taping, jakožto pasivní metoda, zlepšuje cévní zásobení horních končetin jednodušeji než aktivní cvičení, které musí být prováděno pod dohledem fyzioterapeuta.